Involvement of enzyme-substrate charge interactions in the caseinolytic specificity of lactococcal cell envelope-associated proteinases. - Reid, J R (1995)
Three series of oligopeptides were synthesized to investigate the proposal that a major factor in determining the differences in specificity of the lactococcal cell surface-associated proteinases against caseins is the interactions between charged amino acids in the substrate and in the enzyme. The sequences of the oligopeptides were based on two regions of kappa-casein (residues 98 to 111 and 153 to 169) which show markedly different susceptibilities to PI- and PIII-type lactococcal proteinases. In each series, one oligopeptide had an identical sequence to that of the kappa-casein region, while in the others, one or more charged residues were substituted by an amino acid of opposite charge, i.e., His<-->Glu. Generally, substitution of His by Glu in the oligopeptides corresponding to residues 98 to 111 of kappa-casein resulted in reduced cleavage of susceptible bonds by the PI-type proteinase and increased cleavage of susceptible bonds by the PIII-type proteinase. In the case of the oligopeptide corresponding to residues 153 to 169 of kappa-casein, one major cleavage site was evident, and the bond was hydrolyzed by both types of proteinase (even though this sequence in kappa-casein itself is extremely resistant to the PI-type enzyme). Substitution of Glu by His in this oligopeptide, even in the P7 position, resulted in increased cleavage of the bond by the PI-type proteinase and reduced cleavage by the PIII-type proteinase. C-terminal truncation of this oligopeptide resulted in a 100-fold decrease in the rate of hydrolysis of the susceptible bond and a change in the pattern of cleavage.(ABSTRACT TRUNCATED AT 250 WORDS)